Teacher Profession and Professionalism - Ainayya Husna; Anisa Oktaviana; Fery Fadli; Mahariah (LECTURES: Journal of Islamic and Education Studies, 2023)
In the current era, there are many teachers who have been allowed to teach in a school even though the teacher does not yet have one of the criteria as a  professional  teacher,  namely  having  a  diploma.  Therefore  researchers want to examine the professionalism of a teacher which is seen universally from existing schools. In this study, the method used is the method of meta- analysis. Meta-analysis research is a research method that involves collecting, processing, and presenting data in a systematic and objective manner. The purpose of this meta-analysis research is to examine the extent to which teacher competence refers to qualification and competency standards that have  been  established  based  on  Permendiknas No. 16  of 2007.